Emerging Markets Crisis : An Asset Markets Perspective - Krishnamurthy, Arvind; Caballero, Ricardo (Washington, D.C. : International Monetary Fund, 1999)
The entire difference between a mild downturn and a devastating crisis is the occurrence of sharp fire sales of domestic assets and possibly foreign exchange and the ensuing collapse in the balance sheets of both the financial and nonfinancial sector. Why and how do such crises materialize? And why doesn't the private sector take appropriate precautions to avoid the consequences of crises? In this paper we argue that the combination of weak international financial links and underdeveloped domestic financial markets offers a parsimonious account of these and related phenomena present in emerging markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet